1999
DOI: 10.1207/s15327914nc340107
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Plant Foods and Stomach Cancer Mortality in the Seven Countries Study. Is Grain Consumption a Risk Factor?

Abstract: Plant foods are generally considered to be beneficial for health. A higher consumption of fruits, and to a lesser extent vegetables, is consistently associated with a lower risk of stomach cancer. Results on the association between stomach cancer and grain consumption are less clear. We associated plant food consumption with 25-year stomach cancer mortality at population level in the Seven Countries Study. Around 1960, > 12,000 men aged 40-59 years from 7 countries and 16 cohorts were enrolled. In each cohort,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…21 A number of epidemiologic studies, mainly casecontrol investigations, have reported an increased risk of stomach cancer associated with high consumption of starchy foods with high glycemic index, such as white bread, rice and potatoes. [1][2][3][4][5][6] Such foods are also relatively low in antioxidants and other micronutrients that might be protective in stomach carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 A number of epidemiologic studies, mainly casecontrol investigations, have reported an increased risk of stomach cancer associated with high consumption of starchy foods with high glycemic index, such as white bread, rice and potatoes. [1][2][3][4][5][6] Such foods are also relatively low in antioxidants and other micronutrients that might be protective in stomach carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…1 In this regard, several case-control studies have found an increased risk of stomach cancer associated with high consumption of refined grains and starchy foods. [1][2][3][4][5][6] Most refined-grain products and starchy foods are rapidly digested in the gut and have a high glycemic index. 7 The glycemic index is a measure used to rank carbohydrate-containing foods by their glycemic response and, hence, their effects on blood insulin concentrations.…”
mentioning
confidence: 99%
“…Of 11 studies that reported RRs for cancer mortality (11,12,15,16,22,24,35,36,38,44,45), 3 studies reported a protective association (16,44,45), and 8 others did not find any significant association (11,12,15,22,24,35,36,38). All studies except 4 (18,35,36,40) adjusted for age (n = 15). Most cohorts controlled for some conventional risk factors, including BMI (n = 15), smoking (n = 18), and alcohol For adjustments, 1 = age, 2 = BMI, 3 = smoking, 4 = alcohol consumption, 5 = physical activity, 6 = other dietary variables or nutrients, and 7 = total energy intake.…”
Section: Resultsmentioning
confidence: 99%
“…We also did not include 2 studies (33, 34) conducted on patients with heart failure (34) and colorectal cancer (33) in the analysis, because subjects in these studies were not representative of the general population and they might have changed their diets after diagnosis of the disease. Three studies (35)(36)(37) that reported RRs for whole-grain intake as a continuous variable were excluded from the meta-analysis; however, these studies were included in the systematic review. Required information (RRs for highest compared with lowest intake of whole grain or RRs for fatal MI) for these studies could not be obtained even by contacting the authors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation